The Terrorist Aim - Abed, Saif; Abdullah, Firas (Journal of Legal Sciences, 2023)
The aim of human behavior is the psychological element that is no less important than the other psychological elements, and its importance in the formation of human behavior. Raising the subject of the aim came in view of the importance of the aim element in criminal behavior, the terrorist crime as one of the types or forms of that behavior has a specificity that distinguishes it from the rest of the crimes where the role of the criminal aim appears clear and gives the terrorist crime the distinctive element in its moral corner, the Iraqi legislator in the Anti-Terrorism Law No. 13 For the year 2005 explicitly stipulated the terrorist aim, but did not clarify or specify the meaning of the purpose of the jurisprudence of the judiciary, which often confuses the purpose and the motive as well. The meaning of the terminology in jurisprudence and law and a special definition of the criminal aim, since the criminal jurisprudence did not address the topic of defining the criminal purpose in a clear and precise definition, after referring to an important point that the criminal aim is an immoral (criminal) end.